2020
DOI: 10.1007/s00268-019-05355-7
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Acute Care Surgery Patients in Rwanda

Abstract: Introduction Malnutrition is prevalent in hospitalized surgical patients and has been shown to significantly alter outcomes including length of hospital stay, complications, and mortality. Different tools for nutrition assessment were developed and are being used. The aim of this study was to characterize the nutritional status of acute care surgery patients, determine risk factors for malnutrition, and describe outcomes in patients with malnutrition. Methods This was a prospective, descriptive study of malnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 19 publications
0
45
1
1
Order By: Relevance
“…In a recent Brazilian prospective study involving 414 critically ill trauma patients, Ceniccola et al (2020) also demonstrated satisfactory accuracy (area under the curve [AUC] = 0.78; 95% CI, 0.72–0.83), with moderate sensitivity (89.2%), low specificity (66.4%), and a κ coefficient equal to 0.570 16 . Likewise, recently, Abahuje et al (2020) showed a satisfactory accuracy of AND‐ASPEN to identify malnutrition (AUC = 0.75; CI not reported), but also a moderate κ coefficient value (0.529) 17 . The lower agreement between SGA and AND‐ASPEN indicated in the previously cited studies, in comparison with our results, can possibly be explained by the sample, which was composed of acute care patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In a recent Brazilian prospective study involving 414 critically ill trauma patients, Ceniccola et al (2020) also demonstrated satisfactory accuracy (area under the curve [AUC] = 0.78; 95% CI, 0.72–0.83), with moderate sensitivity (89.2%), low specificity (66.4%), and a κ coefficient equal to 0.570 16 . Likewise, recently, Abahuje et al (2020) showed a satisfactory accuracy of AND‐ASPEN to identify malnutrition (AUC = 0.75; CI not reported), but also a moderate κ coefficient value (0.529) 17 . The lower agreement between SGA and AND‐ASPEN indicated in the previously cited studies, in comparison with our results, can possibly be explained by the sample, which was composed of acute care patients.…”
Section: Discussionmentioning
confidence: 95%
“…The large CI for in‐hospital mortality and for 6‐month mortality suggests an imprecise result, which possibly may be explained by the low incidence of death in the sample, in both cases. About 10 studies have been published regarding the evaluation of the predictive validity of the AND‐ASPEN Consensus 16‐19,21‐26,40 . A prospective longitudinal study carried out with 490 oncological and surgical patients from a US hospital described that malnutrition defined by AND‐ASPEN was a predictor of prolonged LOS (odds ratio, 1.67; without description of 95% CI) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported satisfactory levels of accuracy and moderate agreement for the MCC compared to the SGA in adult hospitalized patients 94 , individuals with severe conditions in general, trauma 95 , and surgery patients 96 . In regard to outcomes, the MCC predicted longer hospitalization times 97 and higher care costs 98 .…”
Section: Recommendationmentioning
confidence: 99%